Gall-specific promoter, an alternative to the constitutive CaMV35S promoter, drives host-derived RNA interference targeting Mi-msp2 gene to confer effective nematode resistance - Joshi, Ila; Kumar, Anil; Kohli, Deshika; Bhattacharya, Ramcharan; Sirohi, Anil; Chaudhury, Ashok; Jain, Pradeep K. (Frontiers in Plant Science, 2022)
One of the major obligate plant parasites causing massive economic crop losses belongs to the class of root-knot nematodes (RKNs). Targeting of major nematode parasitism genes via Host Delivered-RNAi (HD-RNAi) to confer silencing is established as one of the most effective approaches to curb nematode infection. Utilizing nematode-responsive root-specific (NRRS) promoters to design a dsRNA molecule targeting approach to hamper nematode parasitism. Here, a previously validated peroxidase gall specific promoter, pAt2g18140, from Arabidopsis was employed to express the dsRNA construct of the nematode effector gene Mi-msp2 from Meloidogyne incognita. Arabidopsis RNAi lines of CaMV35S::Mi-msp2-RNAi and pAt2g18140::Mi-msp2-RNAi were compared with control plants to assess the decrease in plant nematode infection. When subjected to infection, the maximum reductions in the numbers of galls, females and egg masses in the CaMV35S::Mi-msp2-RNAi lines were 61%, 66% and 95%, respectively, whereas for the pAt2g18140::Mi-msp2-RNAi lines, they were 63%, 68% and 100%, respectively. The reduction in transcript level ranged from 79%-82% for CaMV35S::Mi- msp2-RNAi and 72%-79% for the pAt2g18140::Mi-msp2-RNAi lines. Additionally, a reduction in female size and a subsequent reduction in next-generation fecundity demonstrate the efficacy and potential of the gall specific promoter pAt2g18140 for utilization in the development of HD- RNAi constructs against RKN, as an excellent alternative to the CaMV35S promoter.